Hyperventilation Syndrome: Investigating the Relationship Between Nijmegen Questionnaire, Vestibular Function Tests, and Patient Symptoms. Issue 3 (March 2020) - Williams, Christopher Y. K.; Williams, Robert W. K.; Knight, Richard; Hashmi, Syed; Donnelly, Neil; Bance, Manohar
Abstract : Objective: To explore the Nijmegen Questionnaire (NQ) and its relationship to vestibular function tests and symptoms in patients with dizziness; to compare patient characteristics between those with a positive Nijmegen score and patients clinically diagnosed with hyperventilation syndrome (HVS). Study Design: Retrospective case series. Setting: Tertiary neurotology referral center. Patients: Patients seen at vestibular assessment were grouped according to positive (≥24) or negative (<24) Nijmegen scores; secondary analysis was performed on patients grouped by a clinical diagnosis of hyperventilation syndrome. Intervention(s): NQ, vestibular function tests, hospital anxiety and depression scale (HADS), vestibular rehabilitation benefit questionnaire (VRBQ). Main Outcome Measure(s): Medical records of patients presenting for vestibular assessment from January to December 2017 were retrospectively reviewed. Demographic data, self-reported questionnaire results, HVS diagnosis, vestibular test results, and reported symptoms were recorded. Results: In total, 359 patients presented for vestibular assessment with completed NQ. One hundred thirty nine patients (39%) had a positive (≥24) Nijmegen score. In 34 patients, a diagnosis of hyperventilation syndrome was recorded; 10 of these patients did not have a positive Nijmegen score. There was no significant difference found in either vestibular lesion type or compensation status between patients with positive and negative Nijmegen scores ( p > 0.05). Symptoms commonly described by patients with positive Nijmegen scores include "blurred vision, " "tingling, " "anxiety, " "shortness of breath, " "palpitations, " "panic, " "numbness, " "chest pain, " and "chest tightness." In contrast, when grouped by HVS diagnosis, patients with HVS were significantly more likely to have No Lesion detected on vestibular function testing ( p = 0.0366). "Panic, " "anxiety, " and "tingling" were the only significant symptoms reported more often in the HVS diagnosis group, while "nausea/vomiting" and "vertigo" were reported significantly less frequently compared with the non-HVS diagnosis group. Conclusions: Hyperventilation is a complex stimulus, with some effects manifesting in neurotology clinics. This study reveals discrepancies in both vestibular assessment findings and symptom profiles between patients with a positive screening score in the NQ and patients clinically diagnosed with hyperventilation syndrome. This data will inform clinicians' interpretation of the NQ in the neurotologic setting.